A Method of Stability Prediction for Gear Milling - Zhang Kaifei; Jin Gang; Yu Yongchang; Wang Wanzhang (Jixie chuandong)
The milling chatter is a form of self-excited,unstable vibration in the process of machining,which may result in low machining quality,poor accuracy and surface finish,as well as accelerated tool wear,aside from damaging the cutting spindle and machined part.A semi-discretization method for predicting the stability of milling process with multiple time delays to study cutting chatter is presented.Taking the unequal pitch milling as example,the comparison between this method and the existing zero order analysis method is carried out,through the theoretical verification,the proposed method with variable pitch cutter in the spindle between 8 000 to 9 000r/min will obtain greater stability prediction limit,while in other revolution range,two predictive results are in good congruency.